Tetracycline degradation mechanism of peroxymonosulfate activated by oxygen-doped carbon nitride. Issue 10 (22nd February 2023) - Wang, Liquan; Li, Ruyi; Zhang, Yimin; Gao, Yuexiang; Xiao, Xian; Zhang, Zhiwei; Chen, Ting; Zhao, Yuan
Abstract : In this study, oxygen-doped carbon nitride (O–C3 N4 ) was prepared by thermal polymerization and was applied to activate peroxymonosulfate (PMS) for tetracycline (TC) degradation. Abstract : In this study, oxygen-doped carbon nitride (O–C3 N4 ) was prepared by thermal polymerization and was applied to activate peroxymonosulfate (PMS) for tetracycline (TC) degradation. Experiments were performed to comprehensively evaluate the degradation performance and mechanism. The oxygen atom replaced the nitrogen atom of the triazine structure, which improves the specific surface area of the catalyst, enriches the pore structure and achieves higher electron transport capacity. The characterization results showed that 0.4 O–C3 N4 had the best physicochemical properties, and the degradation experiments showed that the 0.4 O–C3 N4 /PMS system had a higher TC removal rate in 120 min (89.94%) than the unmodified graphitic-phase C3 N4 /PMS system (52.04%). Cycling experiments showed that O–C3 N4 has good reusability and structural stability. Free radical quenching experiments showed that the O–C3 N4 /PMS system had free radical and non-radical pathways for TC degradation and that the main active species was singlet oxygen ( 1 O2 ). Intermediate product analysis showed that TC was mineralized to H2 O and CO2 mainly by the ring opening, deamination, and demethylation reactions. The results of this study show that the 0.4 O–C3 N4 /PMS system is simple to prepare and is efficient at removing TC from contaminated water.